Current control of the electron beam formed in the magnetron gun with a secondary-emission cathode - Dovbnya, A.N.; Reshetnyak, N.G.; Zakutin, V.V.; Chertishchev, I.A.; Romasko, V.P.; Dovbnya, N.A. (Вопросы атомной науки и техники, 2013)
Data are reported on electron beam generation and beam current control in two types of secondary-emission cathode magnetron guns. The influence of the magnetic field value and field distribution on the formation of the beam and its parameters has been investigated in the electron energy range between 20 and 150 keV. The influence of local magnetic field variations on the cathode and the electron beam characteristics has been studied. The possibility to control the electron beam current in various ways has been demonstrated. Приведено результати з формування та управління струмом електронного пучка в двох типах магнетронних гармат з вторинно-емісійними катодами. Досліджено вплив розміру та розподілу магнітного поля на формування пучка та його параметри в діапазоні енергій електронів 20…150 кеВ. Вивчено вплив локальної зміни магнітного поля на катоді на характеристики електронного пучка. Показано можливість управління струмом електронного пучка різними засобами. Приведены результаты по формированию и управлению током электронного пучка в двух типах магнетронных пушек с вторично-эмиссионными катодами. Исследовано влияние величины и распределения магнитного поля на формирование пучка и его параметры в диапазоне энергий электронов 20…150 кэВ. Изучено влияние локального изменения магнитного поля на катоде на характеристики электронного пучка. Показана возможность управления током электронного пучка различными способами.